(untitled) (Third Sector Social Economic Review, 2024)
This research was conducted in Esenyurt District, the most densely populated district of Istanbul in 2023. A survey was conducted with the voluntary participation of 344 public employees working in public institutions such as police, hospital, municipality, education, etc. The data obtained were evaluated through SPSS 22.0 statistical program and the effects of motivation on performance and job commitment were examined. In the business literature, there are studies investigating the effects of motivation on employee performance. Most studies have revealed that motivation is effective on performance. However, the effects of motivation on work engagement should be investigated. In the rapidly changing business world, especially after Covid-19, factors such as changing working conditions, implementation of new business models, changing sectors, changing expectations of the markets, etc. directly affect employees. Therefore, the effects of employee motivation on work engagement and performance in organizations are also changing. Firstly, frequency and percentage analyses, mean and standard deviation analyses were conducted. Kurtosis and Skewness values were analyzed to determine whether the research variables were normally distributed. As a result of correlation and regression analyses, acceptance/rejection explanations of the hypotheses subject to the research were made. It has been determined that there are moderate positive significant relationships between motivation, performance and job commitment of public employees, and that motivation affects and increases employees’ performance and job commitment.